Вплив радiацiйного опромiнення на фiзичнi властивостi рiдин - Gavryushenko, D. A.; Taradii, K. V. (Publishing house "Academperiodika", 2019)
Irradiation of condensed media appreciably changes the equilibrium thermodynamic properties of liquid systems; in particular, the thermodynamic equilibrium becomes violated, and the liquid restructuring takes place. The corresponding variations in the physical properties of liquid systems and their consequences have been considered.